Russian Student Readiness for Professional Service: from Actual to Desired - R. A. Zayakina (Высшее образование в России)
The phenomenon of service comes into our area of interest when we are talking about the uniqueness of Russia’s social structure and the markers that define it. Service can be included in everyday life through professional activities, therefore we can consider the subject, focusing on its type. The goal of the research is to determine the meaning of professional service, its place in the modern world, as well as the development of methodological guidelines guiding the training session. Achieving the goal would be impossible without relying on the methodology of the social and philosophical analysis, value, activity, and psychological approaches.The following problems that structure the presentation of the material have been solved. 1. The origins of the idea of service and the ways of its development in Russian society are revealed. Retrospectively the transformation of the ministry is considered from the formation of Russian statehood to modernity. 2. The service strategy for any specialist activity is determined. It is argued that the ethics of every profession can be built around the idea of service. 3. The direction of the formation of students’ attitudes towards an acquired profession based on service is proposed. They are: awareness of the importance of labor; assessment of the work role as a goal; developed social responsibility; acceptance of service as one of life’s principles. 4. Meaningful guidelines are outlined in the discussion of possible difficulties, that may arise on the path of professional service. Such changes include: loss of motivation; loss of professionalism value; refusal of a lifelong professional trajectory. The research is exploratory in nature, but the results obtained turn out to be fruitful for the exchange of the first experience of conducting the course “Fundamentals of Russian Statehood”, and later, theoretical and methodological discussion with possible correction of educational material.